Intelligent Audio-Text Digital Archiving System for Court Proceedings Documentation - Imam Solikin; Nasrullah Nasrullah (Citra Air Nusantara, 2026)
Court proceedings documentation plays a crucial role in preserving legal records and ensuring efficient access to judicial information. However, conventional documentation and archiving processes often rely on manual procedures, leading to inefficiencies, difficulties in information retrieval, and inconsistencies in records management. This study aims to develop an intelligent audio-text digital archiving system for court proceedings to improve the effectiveness and efficiency of judicial record management through the integration of audio and textual data. The system was developed using the waterfall software development model, which consists of the requirements analysis, system design, implementation, testing, and maintenance phases. The proposed system provides functionalities such as audio recording management, text-based documentation, digital data storage, indexing, and search capabilities to facilitate efficient access to archived records. System testing was conducted to evaluate the functionality and usability of the system in supporting court documentation activities. The results indicate that the developed system improves documentation efficiency, simplifies information retrieval, and enhances the accuracy and reliability of court records. Furthermore, the proposed system contributes to the digital transformation of judicial information management by providing a more structured, efficient, and intelligent archiving solution.